Pengaruh Dukungan Pemerintah Dan Partisipasi Masyarakat Terhadap Pengembangan Destinasi Wisata Desa Mepar, Kecamatan Lingga, Kabupaten Lingga - shelvia; Wira , Winata; Jalal, Abdul (Program Studi Manajemen FEBM UMRAH, 2026)
This study aims to analyze the influence of government support and community participation on thedevelopment of the tourist destination of Mepar Village, Lingga District, Lingga Regency. This study used a quantitative approach with a survey method by distributing questionnaires to 97 respondents from the Mepar Village community. Data were analyzed using multiple linear regression with IBM SPSS version 26. The results show that, partially, government support has a positive and significant effect on tourist destination development (t-count 3.741; sig. 0.000<0.05), as does community participation (t-count 3.772; sig. 0.000<0.05). Simultaneously, both variables significantly affect tourist destination development, with an F-count of 144.641 and sig. 0.000<0.05. The Adjusted R Square value of 0.750 indicates that government support and community participation explain 75% of the variation in tourist destination development, while the remaining 25% is explained by other factors outside the model. These findings confirm that synergy between government support and community involvement is a crucial factor in driving the sustainable development of the Mepar Village tourist destination.